WAGES IN ISLAMIC LAW - Abdul Hadi Ismail; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2023)
Allah Almighty created humans as beings who cannot live without helping each other. One of the human activities in Muamalah is wages, in Fiqh it is called Ujrah. Wages are an issue that cannot be solved through discussion by parties or organizations, both private and government. It's as if wages are a task that always makes management think about setting policy. Islam offers the best solution to the wage problem to protect the interests of workers and employers without violating the legal rights of employers. The concept of Wages is established in the most appropriate way without putting pressure on any party. This type of research is descriptive qualitative and uses secondary data collection techniques. The results showed that  the pillars and wage requirements were as follows:  Wages and Workers (Mu'jir and Musta'jir), Shighat (Ijab Qabul), wages or rewards, and the existence of expediency.  Wages can be grouped into two parts, namely as follows: The wages already mentioned (Ajrul Musamma) Y i.e. the wages mentioned at the beginning of the transaction, the condition is that when it is mentioned it must be accompanied by a willingness (received) by both parties, Commensurate wages (ajrul mistli) Is a wage that is commensurate with its work and commensurate with the conditions of work.  In general, the provisions of islamic law regarding the determination of the payment of wages are as follows:  Wages are paid as soon as possible, Wages are given according to their ability and achievements, Wages are mentioned before work begins, and Wages are paid appropriately